Outsourcing In Malaysia: Assessing The Advantages And Disadvantages And Key Success Factors That Influence The Outsourcing Decision - Goh, Thean Siang (2008)
This paper will analyze on manufacturing employees' perception and point of view toward outsourcing activity in Malaysia.